ANALISIS VARIASI PENGGUNAAN SLICE THICKNESS TERHADAP KUALITAS CITRA PADA PEMERIKSAAN CT SCAN SINUS PARANASAL POTONGAN CORONAL DENGAN KLINIS SINUSITIS DI RUMAH SAKIT TK. II PELAMONIA MAKASSAR - Muh. Anjas Irawan Hamzah Anjas; Ni Putu Rita Jeniyanthi Rita; Made Sayang Pratista Sayang (Medical Imaging and Radiation Protection Research Journal, 2023)
Sinusitis is a bacterial infectious disease that patients often complain about to doctors in the ears, nose and throat (ENT). A CT scan is an examination of the choice to see the paranasal sinuses in the axial, sagittal and coronal fields. On the coronal field it is good to display osteomeatal complexes and more informative than axial and sagittal pieces. CT scans have components that affect image quality consisting of spatial resolution, contrast resolution, and noise. Spatial resolution is the ability of a system to distinguish a structure from a very small object with a very adjacent location. Contrast resolution is the ability to distinguish the density or density of the structure of a particular object adjacent to each other. Noise is the standard percentage deviation from the number of pixel values obtained from the result of waterbath imagery. This type of research is quantitative with an experimental approach to analyze the use of slice thickness variations on image quality using variations: 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, and 3 mm. Data collection was carried out in June - July 2022 with 10 samples. Researchers took data on the examination of CT Scans of the paranasal sinuses with clinical sinusitis. With the results of the research conducted, it can be concluded that in the overall friedman test results there is an influence on the use of slice thickness variations on image quality in the paranasal sinus CT scan examination with clinical sinusitis using slice thickness variations. Based on the results of this study, researchers can recommend a paranasal sinus CT scan with clinical sinusitis using a slice thickness of 0.5  mm to get good and optimal image quality results.